IDENTIFICATION OF THE WEST JAVA INTERNATIONAL AIRPORT'S CATCHMENT AREA RELATED TO POTENTIAL AIRPORT LEAKAGE - Sri Dharmestha, Aga
The development of air transportation needs to be supported by an adequate airport. West Java International Airport has been transformed into the main airport in West Java after the relocation of operations. The airport will form a catchment area supported by reliable accessibility to reach it, especially if it is located outside the downtown. Considering that the range of service between airports is prone to overlapping, which triggers airport leakage, a study was conducted to identify the distribution of West Java International Airport’s catchment area related to potential airport leakage. This study compares the distribution of airport catchment areas based on development plans, passenger surveys, and parked vehicle analysis results. The identified catchment area is used to examine the correlation between travel distance to the number of vehicles entering West Java International Airport using exponential regression analysis. Variable with greater significance value is used as the basis for reviewing the service coverage area with network analyst based on standards obtained from the literature reviews. The results can be reviewed to identify potential airport leakage.The research shows that the West Java International Airport has a catchment area extending from Karawang Regency to Tegal Regency with potential expansion into the Greater Jakarta Metropolitan Area and Central Java. Relative distance is a significant factor that influences the interest in using the airport. With an optimal relative distance, the service coverage area can reach almost the entire catchment area, but there is potential for airport leakage due to overlap with other airports, which can impact on market share. This research can be a preliminary review for further studies related to optimization of airport catchment areas by involving other aspects that have the potential to trigger airport leakage